Effectiveness e-authentic assessment in computer network course. (March 2020) - Ambiyar,; Efendi, Raimon; Irawati, Yuyun; Waskito,; Suryadimal,
Abstract: This study aims to identify the quality and effectiveness of the application of authentic web-based assessments in computer network learning on wireless material, and to identify profiles of students' skills and knowledge competencies in learning computer networks on wireless material. The trial was conducted at the Faculty of Computer Science, University of Dharmas Indonesia. This research uses a descriptive method. The population in this study were students of the Informatics Engineering Study Program. Sampling is done using the purposive sampling method. Based on the results of the study, the quality of authentic assessments showed validity for assessment of performance of 0.94 (high) and reliability of 0.93 (very high), while the validity for the description question was 0.97 (very high) and reliability was 0.98 (very high). Based on observations on the effectiveness of the implementation of authentic assessments and student questionnaires, the level of application of authentic assessments is in categories both at the stage of assessment preparation, implementation of assessment and reflection. The skills competency profile of most students is in very good category, while the knowledge competencies of most students fall into sufficient categories for each indicator of the problem.